Bisphosphonate Treatment Alters the Skeletal Response to Mechanical Stimulation in Children With Osteogenesis Imperfecta: A Pilot Study. (1st March 2022) - Sithambaran, Siva; Harrison, Rachel; Gopal‐Kothandapandi, Sujatha; Rigby, Alan; Bishop, Nick
ABSTRACT: Children with osteogenesis imperfecta (OI) are commonly treated with bisphosphonates. We investigated the skeletal response to mechanical stimulation in children with OI before and after bisphosphonate treatment. Twelve children with OI, naïve to bisphosphonate treatment, stood on a high‐frequency (30 Hz), low‐amplitude (50 to 200 μ) vibrating platform (Marodyne LivMD) for 10 minutes daily (2.5 minutes × 4 with interspersed 1‐minute rest periods) for 7 days (whole body vibration [WBV] 1; day (D) 1–7), followed successively by 5 weeks' monitoring without intervention, 6 weeks' risedronate treatment, 1 week of WBV (WBV2; D85–91), and 1 week without intervention (D92–98). Procollagen type I N‐terminal propeptide (P1NP), bone‐specific alkaline phosphatase (BSALP), and carboxy‐terminal telopeptide of type I collagen cross‐link (CTX) were measured at baseline and intervals bracketing periods of vibration and risedronate treatment. Both P1NP and CTX rose to D8 (18.4%, 13.8%, p  < 0.05, respectively), plateaued, then rose again at D43 (19.8%, 19.2%, respectively, p  < 0.05 versus baseline). At D85 (after risedronate) both P1NP and CTX had fallen to pre‐WBV1 levels. A significantly smaller increase in P1NP was found after WBV2 (D85–91) at D92 (3.5%, 9.2%, respectively) and D99 versus after WBV1 (both p  < 0.05). BSALP changed little after WBV1, fell during risedronate, and rose toward baseline after WBV2. We thus showed that WBV increased bone formation and resorption; that increase was attenuated after risedronate. The early increase in P1NP and CTX (D8) after WBV1 suggests increased osteoid formation within existing remodeling units but not increased mineralization. Later increases in P1NP/CTX (D42) suggest increased remodeling cycle initiation after WBV. Risedronate suppressed both biomarkers. The lower increase in P1NP/CTX after WBV2 suggests limited capacity to increase osteoid formation from existing "early stage" osteoblasts and a possible "hangover" effect of risedronate on remodeling activation. These results provide insights into both the response to WBV, ie, mechanical stimulation, and the effect of antiresorptive therapy in children with OI. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.